Pickleball: Review and Clinical Recommendations for this Fast-growing Sport. Issue 10 (October 2020) - Vitale, Kenneth; Liu, Steven
Abstract : Abstract: Pickleball is a single or doubles volley sport played with paddles and ball on a hardcourt. Growing in popularity in recent years, injuries can occur similar to racquet sports; however, there is a scarcity of references in the literature for sports medicine providers encountering these athletes and injuries. This review provides clinicians treating pickleball athletes with an overview of the sport, a case study demonstrating the significant injuries that can occur in pickleball, and a review of the available literature. We provide a discussion on common pickleball injuries, injury prevention strategies, and event coverage recommendations to better equip sports medicine providers with a base of knowledge and a clinical approach to treat these athletes, or "picklers, " who enjoy this fast-growing sport. Abstract : Pickleball is a fast-growing sport with clear injury risk. This review summarizes injuries, prevention strategies, and event coverage.